2022
DOI: 10.3390/nu14081644
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged or Transition to Metabolically Unhealthy Status, Regardless of Obesity Status, Is Associated with Higher Risk of Cardiovascular Disease Incidence and Mortality in Koreans

Abstract: The risk of chronic disease and mortality may differ by metabolic health and obesity status and its transition. We investigated the risk of cardiovascular disease (CVD) and cancer incidence and mortality according to metabolic health and obesity status and their transition using the nationally representative Korea National Health and Nutrition Examination Survey (KNHANES) and the Ansan-Ansung (ASAS) cohort of the Korean Genome and Epidemiology Study. Participants that agreed to mortality linkage (n = 28,468 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Assessment of metabolic health and obesity varied across studies. Six studies considered five components for determination of metabolic health, including blood pressure, plasma glucose, HDL-cholesterol, triacylglycerols, and waist circumference [ 27 , 28 , 30 , 32 , 34 , 35 , 37 ]; eight studies considered four components, including blood pressure, plasma glucose, HDL-cholesterol, and triacylglycerols [ 25 , 26 , 29 , 31 , 32 , 38 40 ]; one study examined four components, including blood pressure, plasma glucose, triacylglycerols, and waist circumference [ 33 ]; the remaining two studies examined three components [ 9 , 36 ]. Overweight/obesity was defined as BMI ≥ 24 kg/m 2 in five studies [ 25 , 28 , 30 , 31 , 33 ], ≥ 30 kg/m 2 in two studies [ 29 , 39 ], and ≥ 25 kg/m 2 in the remaining studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of metabolic health and obesity varied across studies. Six studies considered five components for determination of metabolic health, including blood pressure, plasma glucose, HDL-cholesterol, triacylglycerols, and waist circumference [ 27 , 28 , 30 , 32 , 34 , 35 , 37 ]; eight studies considered four components, including blood pressure, plasma glucose, HDL-cholesterol, and triacylglycerols [ 25 , 26 , 29 , 31 , 32 , 38 40 ]; one study examined four components, including blood pressure, plasma glucose, triacylglycerols, and waist circumference [ 33 ]; the remaining two studies examined three components [ 9 , 36 ]. Overweight/obesity was defined as BMI ≥ 24 kg/m 2 in five studies [ 25 , 28 , 30 , 31 , 33 ], ≥ 30 kg/m 2 in two studies [ 29 , 39 ], and ≥ 25 kg/m 2 in the remaining studies.…”
Section: Resultsmentioning
confidence: 99%
“…Overweight/obesity was defined as BMI ≥ 24 kg/m 2 in five studies [ 25 , 28 , 30 , 31 , 33 ], ≥ 30 kg/m 2 in two studies [ 29 , 39 ], and ≥ 25 kg/m 2 in the remaining studies. Five studies examined transition of metabolic health and adiposity status prior to initiation of follow-up [ 9 , 26 , 32 , 37 , 40 ], five studies examined transition during the early phase of follow-up (mainly within the first 3–8 years) [ 27 , 29 , 33 , 34 , 36 ], and seven studies examined transition over the entire follow-up period from baseline to the end of follow-up [ 25 , 28 , 30 , 31 , 35 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our study revealed that BMI was an important risk factor associated with changes in prediabetes status. Previous studies 25,26 suggested that the transition to metabolic unhealthiness (such as the onset of type 2 diabetes) substantially increases the risk of death among individuals with obesity. Because several other metabolic health factors, such as hypertension and hyperlipidemia, might confound the association between changes in prediabetes status and risk of death, we further adjusted for hypertension and total cholesterol level and found no substantial differences in the results.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for this discrepancy lies in the definition of “metabolic health”, which demands no metabolic syndrome manifestations presented according to their diagnostic criteria, while most international standards require less than 2. 6 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for this discrepancy lies in the definition of "metabolic health", which demands no metabolic syndrome manifestations presented according to their diagnostic criteria, while most international standards require less than 2. 6,25,26 More recently, the China Kadoorie Biobank and the China XinJiang cohort study, including 458,246 and 5,059 Chinese adults, respectively, showed that MHO individuals were at an increased risk of CVD (HR 1.54, 95% CI 1.49-1.60 and HR 2.60, 95% CI 1.93-3.49) than their MHNW counterparts. 3,27 On the basis of these studies, the strength of our study was that the cohort was well characterized, the laboratory data were complete at baseline and follow-up and the uniform definition was defined according to the Joint Interim Statement (JIS).…”
Section: Discussionmentioning
confidence: 99%